Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/jeb.13402
|View full text |Cite
|
Sign up to set email alerts
|

Costs of weaponry: Unarmed males sire more offspring than armed males in a male‐dimorphic mite

Abstract: Morphological structures used as weapons in male–male competition are not only costly to develop but are also probably costly to maintain during adulthood. Therefore, having weapons could reduce the energy available for other fitness‐enhancing actions, such as post‐copulatory investment. We tested the hypothesis that armed males make lower post‐copulatory investments than unarmed males, and that this difference will be most pronounced under food‐limited conditions. We performed two experiments using the male‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…Our results align well with evidence from horned beetles that larger males are generally more successful fighters than smaller males (Emlen 1997;Hongo 2007;McCullough and Simmons 2016;Mitchem et al 2019), so that small males resort to sneaking behaviour to gain access to females, adaptively expressing a different, weaponless morphology (Moczek and Emlen 2000). We currently do not have evidence that R. robini scramblers are sneakers, but they have been shown to obtain higher fertilization success from a single copulation than fighters (Van den Beuken et al 2019). Furthermore, scramblers move quicker than fighters and are better able to navigate spatially complex environments (Tomkins et al 2011), which could benefit a hypothetical sneaking tactic.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results align well with evidence from horned beetles that larger males are generally more successful fighters than smaller males (Emlen 1997;Hongo 2007;McCullough and Simmons 2016;Mitchem et al 2019), so that small males resort to sneaking behaviour to gain access to females, adaptively expressing a different, weaponless morphology (Moczek and Emlen 2000). We currently do not have evidence that R. robini scramblers are sneakers, but they have been shown to obtain higher fertilization success from a single copulation than fighters (Van den Beuken et al 2019). Furthermore, scramblers move quicker than fighters and are better able to navigate spatially complex environments (Tomkins et al 2011), which could benefit a hypothetical sneaking tactic.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, small and poorly-fed males tend to develop an unmodified third leg pair, which is morphologically similar to the other legs (the 'scrambler' phenotype) (Radwan 1995;Smallegange 2011). Fighter males are more aggressive than scrambler males (Radwan et al 2000), and can monopolize females by killing rivals (Radwan and Klimas 2001), while scramblers have a mobility advantage (Tomkins et al 2011) and can obtain higher fertilization success from a single copulation ( Van den Beuken et al 2019). Male morph expression depends on body size immediately prior to metamorphosis, with larger males becoming fighters and smaller males scramblers (Radwan 1995;Smallegange 2011), although adult fighter males are on average not larger than adult scrambler males (Smallegange et al 2012); fighters shrink during metamorphosis while scramblers do not (Radwan et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The trade-off between weapons critical for precopulatory mating success and traits critical for postcopulatory fertilization success has now been demonstrated in a number of species. Males that lack weapons tend to have increased fertilization success (Joseph et al, 2018;Somjee et al, 2018;Van den Beuken et al, 2019). Males that invest in precopulatory traits may not be able to fully invest in postcopulatory traits (Parker et al, 2013;Parker & Pizzari, 2010;Simmons et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…[100] In the male dimorphic bulb mite, Rhizoglyphus robini, fighter-males with exaggerated leg weapons consistently sire less offspring compared to scrambler males without these weapons regardless of different nutrient intakes during adulthood. [101] While a number of studies have revealed allocation trade-offs with the investment of weapons relative to other traits during development, [95,102] far fewer examine the ways in which energy may trade-off among traits in adults. Future studies that relate energy budgets to the behavior and reproductive outputs for individuals of different size, or sexually selected trait size have the potential to uncover yet unidentified energetic constraints that may be shaping exaggerated sexually selected traits.…”
Section: The Energetic Costs Of Sexually Selected Traits Do Not End With Growthmentioning
confidence: 99%